2002
DOI: 10.1577/1548-8675(2002)022<1358:uoeemf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Exploitation Estimates Made from Tag Returns

Abstract: Over 6,000 crappies Pomoxis spp. were tagged in five water bodies to estimate exploitation rates by anglers. Exploitation rates were computed as the percentage of tags returned after adjustment for three sources of uncertainty: postrelease mortality due to the tagging process, tag loss, and the reporting rate of tagged fish. Confidence intervals around exploitation rates were estimated by resampling from the probability distributions of tagging mortality, tag loss, and reporting rate. Estimates of exploitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 25 publications
5
69
1
Order By: Relevance
“…With this function, chronic shedding was near zero for the first 5 months after tagging, and then progressively increased during the next several months before stabilizing at a shedding rate of 31% at 12 months post-tagging. This pattern in chronic shedding, as well as the rates associated with handling mortality and immediate shedding, corresponded to our observations in the lake whitefish study (see Ebener et al, 2010a), and are similar to rates that have been reported in the literature (Ebener and Copes, 1982;Muoneke, 1992;Pierce and Tomcko, 1993;Fabrizio et al, 1996;Hearn et al, 1999;Buzby and Deegan, 1999;Pollock et al, 2001;Miranda et al, 2002;Polacheck et al, 2006;and Taylor et al, 2006). We considered two spatial patterns of reporting rates in our datagenerating model.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…With this function, chronic shedding was near zero for the first 5 months after tagging, and then progressively increased during the next several months before stabilizing at a shedding rate of 31% at 12 months post-tagging. This pattern in chronic shedding, as well as the rates associated with handling mortality and immediate shedding, corresponded to our observations in the lake whitefish study (see Ebener et al, 2010a), and are similar to rates that have been reported in the literature (Ebener and Copes, 1982;Muoneke, 1992;Pierce and Tomcko, 1993;Fabrizio et al, 1996;Hearn et al, 1999;Buzby and Deegan, 1999;Pollock et al, 2001;Miranda et al, 2002;Polacheck et al, 2006;and Taylor et al, 2006). We considered two spatial patterns of reporting rates in our datagenerating model.…”
Section: Methodssupporting
confidence: 83%
“…As a result, accurate mortality estimation using a tag-recovery approach at least partly depends on the collection of auxiliary data pertaining to tag shedding (hereafter referred to as shedding), handling mortality, and tag reporting (hereafter referred to as reporting). Each of these factors can be measured in a variety of ways: shedding can be estimated by double tagging or supplemental marking of fish (Pierce and Tomcko, 1993;Fabrizio et al, 1999;Latour et al, 2001;Miranda et al, 2002, Livings et al, 2007; handling mortality can be estimated by withholding samples of tagged fish in tanks, pens, or cages (Pierce and Tomcko, 1993;Latour et al, 2001;Miranda et al, 2002;Taylor et al, 2006); reporting rates can be estimated through the use of highreward tags Pollock et al, 2002;Taylor et al, 2006), planted tags (Hearn et al, 2003), or creel or port surveys (Hearn et al, 1999;Pollock et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporting rates can be problematic when relaying on anglers for recapture information (Miranda et al, 2002). To maximize angler reporting of tags, most rewards given out during the first year were either $20 or $50, to spur interest and participation by anglers (Pollock et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biologists and managers can prevent a large waste of resources by conducting preliminary evaluations on possible tagging study designs. Recovery of tags is affected by a variety of factors, including tagging levels, issues with the tagging process (e.g., tag shedding, handling mortality), fishery characteristics (e.g., tag non-reporting, level of harvest), and fish population dynamics (e.g., movement patterns, natural mortality) (Fabrizio et al, 1996;Hoeing et al, 1998;Latour et al, 2001;Miranda et al, 2002). Because of this, it is important to examine accuracy and precision of parameter estimates across a range of design features, and stochastic simulations, such as those employed herein, have been identified as useful in this regard .…”
Section: Discussionmentioning
confidence: 99%